Evaluating Institutional Capability of Nepali Grassroots Organizations for Service Delivery Functions - Acharya, Keshav Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2017)
Grassroots organizations are well situated to deliver the services and implement the development activities at community level in Nepal. The development of grassroots organizations on the one hand enables the effective service delivery while it enhances community governance system on the other. This study analyses the institutional capability of grassroots level organizations in relation to their service delivery and the study is based on primary and secondary data. One hundred and ten grassroots level organizations were chosen for organizational survey, and three focus group discussions were employed to supplement survey data. The Composite Index (CI) method was employed to analyze the data that shows overall capability of grassroots organizations remained efficient (CI = 0.77). Empirical findings indicate that many grassroots organizations were more committed to work as agents of change through institutional norms, rules and values. Nevertheless, some grassroots organizations were facing institutional crises, influenced by socio-economic power structure, and resource paucity. Following the discussion of results, this study recommends governance measure for efficient capability of grassroots organizations.Dhaulagiri Journal of Sociology and Anthropology Vol.11, 2017; 60-95